2014
DOI: 10.1016/j.abb.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric effects of cardiac troponin TNT1 mutations on actomyosin binding: A novel pathogenic mechanism for hypertrophic cardiomyopathy

Abstract: The majority of hypertrophic cardiomyopathy mutations in (cTnT) occur within the alpha-helical tropomyosin binding TNT1 domain. A highly charged region at the C-terminal end of TNT1 unwinds to create a flexible “hinge”. While this region has not been structurally resolved, it likely acts as an extended linker between the two cTnT functional domains. Mutations in this region cause phenotypically diverse and often severe forms of HCM. Mechanistic insight, however, has been limited by the lack of structural infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…This behavior, together with the increase in resting tension, suggests that in E163R sarcomeres, the thin filament may not turn off properly upon Ca 2+ removal and may be unable to fully maintain its switched‐off state during diastole, in analogy with previously described HCM‐related tropomyosin mutations . The modest increase in myofilament Ca 2+ sensitivity in E163R myocardium is in line with previous findings and may be a consequence of the impaired thin filament blocked state that allows recruitment of some force‐generating crossbridges at low Ca 2+ . We excluded that the increase of myofilament Ca 2+ sensitivity depended on a reduction of troponin I phosphorylation at the protein kinase A site (Figure ), although we have not explored other possible posttranslational modifications of sarcomere proteins (eg, MyPBC3).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This behavior, together with the increase in resting tension, suggests that in E163R sarcomeres, the thin filament may not turn off properly upon Ca 2+ removal and may be unable to fully maintain its switched‐off state during diastole, in analogy with previously described HCM‐related tropomyosin mutations . The modest increase in myofilament Ca 2+ sensitivity in E163R myocardium is in line with previous findings and may be a consequence of the impaired thin filament blocked state that allows recruitment of some force‐generating crossbridges at low Ca 2+ . We excluded that the increase of myofilament Ca 2+ sensitivity depended on a reduction of troponin I phosphorylation at the protein kinase A site (Figure ), although we have not explored other possible posttranslational modifications of sarcomere proteins (eg, MyPBC3).…”
Section: Discussionsupporting
confidence: 78%
“…All experimental protocols were performed in agreement with current Italian and European regulations and were approved by the local institutional review board and the animal‐welfare committee of the Italian Ministry of Health. We used a total of sixty‐seven 6‐ to 8‐month‐old male C57BL/6N transgenic mice carrying the R92Q or E163R mutation in the TNNT2 gene, as well as wild‐type (WT) littermates: 22 R92Q, 24 E163R, and 21 WT mice were used for the experiments described below. The mouse colonies were housed in the animal facility of the University of Florence and all experiments were conducted locally.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Moore and colleagues examined the tropomyosin-binding region of cardiac troponin T, a region that harbors severe and phenotypically diverse HCM mutations (Moore et al, 2014). In vitro motility assays showed that specific mutations in cardiac troponin T disrupted weak electrostatic interactions between the thin filament and myosin.…”
Section: The Thin Filamentmentioning
confidence: 99%
“…In vitro motility assays showed that specific mutations in cardiac troponin T disrupted weak electrostatic interactions between the thin filament and myosin. Complementary in vivo data indicates that these same mutations cause cardiac remodeling and disarray of the myofiber, suggesting that the weak cross-bridge formation causes destabilization of the myofilament structure ultimately resulting in disease (Moore et al, 2014). …”
Section: The Thin Filamentmentioning
confidence: 99%